Advanced Mathematical Model of Transfer and Diffusion Process of Harmful Substances in the Atmospheric Boundary Layer - Ravshanov, Normanmad; Sharipov, Daler (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
In the paper, we describe a mathematical model of the spread of harmful substances in the atmospheric boundary layer, taking into account the terrain and the characteristics of the underlying surface, described by means of a system of differential equations in partial derivatives and corresponding initial and boundary conditions. The equations of motion of multicomponent air, equations for calculating the pressure and heat flow for gas and condensate are used in the model. u v w , To determine the velocities of the air mass in the atmosphere in three directions and we consider the hydrodynamic equations of Navier-Stokes, and to compute the density of substances emitted into the atmosphere, taking into account the law of conservation of mass to the fluid flow through the fixed volume we use mass continuity equation. To calculate the heat transfer in a multicomponent environment in the transfer of heat to the gas, and to determine the vapor pressure in terms of temperature, we use the equation ofMendeleev-Clapeyron. The equations are given for describing the transition of water from liquid to gaseous state and vice versa, and when gas, water vapor, liquid water and soot are thrown from the source.